The COLOMBIAN EDUCATION BASED ON THE HOLISTIC MODEL OF PEDAGOGICAL MANAGEMENT ZC: A LOOK TOWARD THE FUTURE - Ureña, Yan; Antolinez, Antolinez (Revista Arbitrada Formación Gerencial, 2022)
This article aims to analyze the Colombian education based on the holistic model of pedagogical management ZC as a way of pedagogical development of the future. This article is based on a qualitative approach, based on document analysis. It is also based on the type of descriptive analytical research, since the purpose is to describe situations and facts, as presented in the reality prevailing at the time of the inquiry. Likewise, it has a non-transectional experience, since the variables are not manipulated in addition to being done in a single moment. Based on the above, it will be carried out in a simple table showing specific characteristics of the following documents for Holistic Model of pedagogical management: Gluyas, Esparza, Romero and Rubio Barrios (2015), Calixto and Álvarez (2012), Tables (2016). We conclude the integration of the model based on the premise that we are not educating the new generations of young people in the whole of their being, in all its dimensions considering the potential for their development. Likewise, educational management must establish the conditions and processes necessary to foster the knowledge management culture within the institution, generating new projects linking the community to the institutional work.